The effect of mindfulness program on general health of patients undergoing hemodialysis - Maryam Moosavi Nejad; Nahid Shahgholian; Rahele Samouei (Wolters Kluwer Medknow Publications, 2018)
Introduction: Patients undergoing hemodialysis have a low level of health and mindfulness technique in mind-body medicine is used to help patients with chronic illness. Therefore, this clinical trial was conducted to determine the effect of the mindfulness program on the general health of patients undergoing treatment with hemodialysis. Methods: Sixty hemodialysis patients were selected through the convenient method and randomly divided into experimental and control groups. Both groups completed demographic information questionnaire and general health questionnaire. Then, the experimental group received 8 sessions of mindfulness training and the control group received 8 sessions of education in relation to end-stage renal disease and hemodialysis. Educational sessions were performed for both groups in the second 30 min after hemodialysis for 1 h in six individual sessions and two 1.5 h group sessions. Immediately after and 1 month after the intervention, the General Health Questionnaire was completed by both groups. Results: Analysis of the findings showed no significant differences between the mean score of general health disorder and its subscales before the intervention in to two groups (P > 0.05). Nevertheless, after intervention in the experimental group, the mean of general health disorder score decreased from 44.17 ± 12.32 to 21.9 ± 6.4 and 1 month after the intervention, the mean score of this score was 23.6 ± 6.2. The mean score of physical symptoms, anxiety and sleep disorder, social functioning deficiency, and depression were also significantly lower in the experimental group immediately after intervention and 1 month after the intervention; however, there were no significant differences between the mean of this score immediately and 1 month after the intervention. In addition, the mean score of general health disorder changes immediately and 1 month after the intervention in the experimental group was significantly more than the control group. In the control group, there was no significant difference between the mean score of general health disorder and its subscales before, immediately, and 1 month after the intervention (P > 0.05). Conclusions: The results of this research showed that mindfulness has been effective in reducing physical and anxiety symptoms, sleep disorder, social dysfunction, and depression symptoms. Therefore, the use of mindfulness as a complementary treatment can improve the general health level in these patients.